(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The process of formation of the teaching methodology of pedagogy is related to the development of pedagogy as an educational subject. Experiences are collected from the initial stages of teaching pedagogy, they are summarized and systematized. Based on them, separate rules and principles are formed, methodical recommendations are created on some issues of training. Based on the generalization of experiences, research is conducted, as a result of which specific aspects of the teaching methodology are determined. The teaching methodology of pedagogy is a synthesis of theory and practice.